Opportunities to develop language skills in Czech lower-secondary English classes: Separated or integrated approach? - Simona Šebestová; Petr Najvar; Tomáš Janík (Czech Pedagogical Society, 2011)
Contemporary approach to foreign language education is based on the communicativeapproach and the communicative competence as its goal. The questionis, to what extent the goals are reflected in foreign language classes. The aim ofthe presented empirical study was to explore the quantity of opportunities whichpupils have to develop language skills (listening, speaking, reading, writing) in Czechlower-secondary English classes. The research employs a video-based methodology.A research instrument - a system of categories based on the concept of language skillswas developed. The research findings showed that pupils had more opportunities to usereceptive skills (reading, listening) than productive skills (speaking, writing). Receptiveskills were more often than productive skills used in separation. All language skills wereoften used in integration but there were not many opportunities for pupils to engage inmore complex activities integrating three or four language skills.